Deteksi dan Analisis Faktor Risiko Hipertensi pada Karyawan di Lingkungan Universitas Sriwijaya - Utama, Feranita; Sari, Desri Maulina; Ningsih, Windi Indah Fajar (Faculty of Medicine, Universitas Andalas, 2021)
Office workers are one group with a high proportion of hypertension compared to other types of work. Objectives: To determined the proportion of pre-hypertension, hypertension and risk factors for hypertension among employees in Sriwijaya University. Methods: This study used a cross-sectional design at Sriwijaya University, and samples were taken from 4 faculties totaling 152 respondents. Sampling using cluster random sampling technique. Data were collected from September to October 2020. The analysis was carried out in univariate, bivariate and multivariate analysis with logistic regression tests. Results: There were 13.2% of employees had hypertension, 40.8% had pre-hypertension, and the risk factor for hypertension among employees was age (p-value = 0.01; OR = 4.76; CI 1.50 <OR <15, 10) after controlling for the variables of the length of work, marriage status and cholesterol levels. Conclusion: There are more than 50% of employees are in a condition of pre-hypertension and hypertension, with age as the main risk; for this reason, employees who are 45 years old are expected to carry out routine health checks with the facilitation of the university and be able to implement the Dietary Approach to Stop hypertension in employees with pre-hypertension / hypertension.Keywords: Â DASH, hypertension, pre-hypertension, the risk factor